Streptozotocin induces neurite outgrowth via PI3K-Akt and glycogen synthase kinase 3Î² in Neuro2a cells - Nishimoto, T.; Kimura, R.; Matsumoto, A.; Sugimoto, H. (Cellular and Molecular Biology, 2016)
Streptozotocin (STZ), a naturally occurring chemical, is toxic to the various kinds of cells such as insulin-producing beta cells. However, the beneficial effect of STZ on neuronal cells such as neurite outgrowth-inducing activity has been unknown. In this study, we examined the effect of STZ on neurite outgrowth in mouse neuronal Neuro2a cells. STZ (0.01 mM 5 mM) exerted remarkable neurite outgrowth-inducing activity in Neuro2a cells in a concentration dependent manner. STZ also had the same neurite outgrowth-inducing activity as that of retinoic acid (RA), which is well known neurite outgrowth inducer. As with the result of RA treatment, STZ administration increased MAP2-positive cells. The MAP2-positive cells reflect neurite outgrowth-induced cells. STZ (0.01 mM 5 mM) did not induce cell death, but significantly decreased cell proliferation. The serine/threonine kinase Akt, a downstream target of phosphatidylinositol-3 kinase (PI3K), was transiently phosphorylated at Ser473 and at Thr303 by STZ (5 mM) administration. Glycogen synthase kinase 3Î² (GSK3Î²), which has been reported to be inactivated by Akt, was also transiently phosphorylated at Ser9 by STZ (5 mM) administration. In addition, a blocker of PI3K, LY294002 (10 Î¼M), significantly attenuated STZ-induced neurite outgrowth. These results suggest that STZ induces neurite outgrowth via activation of PI3K-Akt signaling pathway and GSK3Î² inhibition.